Enhance the Performance of Virtual Machines by Using Cluster Computing Architecture - Chia-Ying Tseng; Kang-Yuan Liu; Liang-Teh Lee (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Virtualization is a very important technology in the IaaS of the cloud computing. User uses computing resource as a virtual machine (VM) provided from the system provider. The VM's performance is depended on physical machine. A VM should be deployed all required resources when it is created. If there is no more resource could be deployed, the VM should be move to another physical machine for getting higher performance by using VM's live migration. The overhead of a VM's live migration is 30 to 90 seconds. If there are many virtual machines which need live migration, the cost of overhead will be very much. This paper presents how to use cluster computing architecture to improve the VM's performance. It will enhance 15% of per-formance compared with VM's live migration. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2486